(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In a forest of Pinus nigra Amold, a tota! of 67 egg batches of two generations of Thaumetopoea pityocampa (Den. & Schiff.) were collected at Janino, Kardjali County, in 1995 and 1996. Directly after sampling the batches were put singly in test tubes with cotton stoppers and held under Iaboratory conditions at 20-22°C. Oviposition always started from the base towards the tip of the needles. After removal of the scales, the numbers of caterpillars hatched were counted. The emergence of egg parasitoids were controlled daily, they were removed and put into small capsules for identification. The final analysis was made after termination of parasitoid emergence. For that ali eggs were opened carefully. The impact of the parasitoid species was evaluated by their meconia and other remains. The average number of eggs per batch was 200 from which 66-72% developed to hatching caterpillars. The number of parasitized eggs amounted to 24-27%. Six species of parasitoids were identified: Baryscapus servadeii (Dom.), Ooencyrtus pityocampae (Mercet), Anastatus bifasciatus (Fonsc.), Baryscapus transversalis Graham, Trichogramma embryophagum (Htg.), and Pediobius sp. The most frequent parasitoid was B. servadeii (82-92.5% of the total parasitoids counted) emerging mainly after hibernation. The high percentage (17.6%) of female A. bifasciatus was surprising reaching maturity.